Rebecca of Sunnybrook Farm - Wiggin, Kate Douglas Smith, 1856-1923. (New York : Dell, 1990)
Talkative, ten-year-old Rebecca goes to live with her spinster aunts, one harsh and demanding, the other soft and sentimental, with whom she spends seven difficult but rewarding years growing up.
"Dell Yearling classic.".
Child Study Children's Book Committee.
Wilson's Children.
6.0
5-8
Keywords: Aunts -- Fiction; Aunts -- Fiction; New England -- Fiction; New England -- Fiction